Ghanaian media coverage of violence against women and girls: implications for health promotion - Ebenezer Owusu-Addo; Sally B. Owusu-Addo; Ernestina F. Antoh; Yaw A. Sarpong; Kwaku Obeng-Okrah; Grace K. Annan (BMC, 2018)
Abstract Background Violence against women and girls (VAWG) is an important public health issue. Framing studies indicate that how the news media cover public health issues is critical for designing effective health promotion interventions. Notwithstanding this, there is little research particularly in low-and middle-income country context examining how the news media frame VAWG. This paper examines news coverage of VAWG in Ghana, and the implications of this for health promotion. Methods This study used frame analysis as the methodological framework in examining how VAWG in Ghana is represented by the media. Qualitative content analysis approach to frame analysis was performed on 48 news articles which constituted the unit of analysis. Results The findings indicate that media framing of VAWG was episodic in nature as the acts of violence perpetrated against women and girls were presented as individual cases without reference to the wider social contexts within which they occurred. Similarly, victim blaming language was largely used in the news articles. In framing VAWG as an individual incident and women as helpless victims, the media fail to shape society's perception of VAWG as a social and public health issue. Conclusions For the media in Ghana to contribute to the prevention of VAWG, there is the need for news coverage to focus on social construction of the issue, and also raise awareness about support services available to victims.